Identification of Bacteria from Skin Swab in Pre-operative Closed Fracture Orthopedic Surgery Patients at Dr. Hasan Sadikin General Hospital - Ghita Bengtissen; Sunarjati Sudigdoadi; Yoyos Dias Ismiarto; Isa Ridwan (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Surgical site infection (SSI) is the most frequent site of health care- associated infections (HAIs). Surgical incision breaks the protective barrier of the skin and causes bacteria to enter; therefore, pre-operative procedure is very important to reduce the risk of SSI. This study aimed to identify any bacteria in skin swab of pre-operative closed fracture during elective orthopedic surgery patients.Methods: This was a descriptive laboratory study, conducted in the Department of Microbiology, Faculty of Medicine, Universitas Padjadjaran in October to November 2012. Samples were taken from skin swab of patients with closed fracture taken before elective orthopedic surgery. Samples were cultured on blood agar, then incubated in an aerobic condition for 24 hours at 37°C. The bacteria were then identified, including the type and the number of the bacteria colonies, using microscopic gram staining and by biochemistry testing using coagulase, novobiocin, and catalase test. The bacteria colonies formed on blood agar were counted using CFU/mL. Results: Of 24 samples taken, 14 (58.3%) were positive for bacteria, 7 negative and 3 were excluded due to dead bacteria. The bacteria identified in the samples were all staphylococcus species and the colony counting was lower than 10⁵ CFU/mL.Conclusions: Bacteria staphylococcus are detected from more than half of skin swab during pre-operative closed fracture orthopedic surgery patients. Thus, it is important to apply a proper antiseptic procedure before making a surgical incision to reduce the risk of SSI.